Influence of zeolite exchanged ammonium on the growth of Ipomoea aquatica - Nik Malek, Nik Ahmad Nizam (2015)
Natural zeolite from Indonesia that was initially exchanged and enriched with ammonium cations was studied for its effect on the growth of Ipomoea aquatica. The retaining of ammonium cations inside the zeolite framework was to ensure that the release of N source (ammonium) can be controlled and prevented the leaching phenomena which can affect our environment. Zeolite and ammonium-zeolite were characterized for their structure using Fourier transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD). These characterizations proved that the structure of zeolite was not distorted after exchanged with ammonium since the exchanged process occurred through ion exchange without the involvement of the main aluminosilicate framework structure of zeolite. The influence of ammonium-zeolite on the growth of I. aquatica was studied in a potted technique and it was compared with parent zeolite and urea. The plant growth study indicated that the growth and yield (Fresh mass) of the studied plant was clearly increased after the usage of ammonium-zeolite as fertilizer compared to that of parent zeolite and urea although the ammonium released study showed similar amount of ammonium released from ammonium-zeolite and urea. This finding indicates the necessity of controlling the release of nutrients for the uptake of plant for a sustainable agriculture and environment and it can be done by using natural zeolite as a carrier system for N source especially ammonium ions.